Orthopedic examination of junior female wrestlers: a case study - Podlivaev, B. A.; Kurashvili, V. A.; Gaiduk, A. A. (International Journal of Wrestling Science, 2021)
Background: The aim of this study was to investigate the possible influence of female wrestling on the musculoskeletal system of junior female wrestlers. Method: The study involved 16 freestyle junior female wrestlers. Orthopedic examination was carried out by optical topography Formetric 4D measurements. Results: Of the 16 subjects of the sample, 12 children were orthopedically normal, 3 patients had false scoliosis and 1 has adolescent idiopathic scoliosis (AIS). The results obtained revealed that contralateral side of deviation of the curve of the spine in subjects with scoliosis is statistically significant (p = 0.002). Furthermore, the relationship between lower midline and contralateral side of deviation of the curve of the spine in patients with false scoliosis is statistically significant (p = 0.003). Conclusions: The Formetric 4D provides a safe method to monitor and track the progression of postural deformities in young athletes. It can be reliably used in the surveillance of patients with AIS.